Openness and innovation within organizations: An empirical analysis of the transformation process of romanian enterprises - Tünde Baga; Diether Gebert (Journal for East European Management Studies, 2005)
In this study, the authors examine how societal and industrial sector-specific peculiarities moderate the translation of intra-organizational openness into innovativeness. A sample comprising N = 24 subsystems from privatized Romanian natural gas companies and N = 26 subsystems from privatized Romanian mechanical engineering companies was analyzed. With this study, the authors aim to contribute to answering the question which industrial sectorspecific conditions are conducive to success given the current societal and economic conditions in Romania. The findings indicate that in the mechanical engineering industry, there is a linear connection between opening processes and success, while this relationship is of a curvilinear nature in the natural gas industry. – – In dieser Studie gehen die Autoren der Frage nach, auf welcher Weise gesamtgesellschaftliche und branchenspezifische Besonderheiten die Übersetzung innerbetrieblicher Öffnung in Innovativität moderieren. Hierfür wurden 24 Subsysteme aus bereits privatisierten rumänischen Gasunternehmen und 26 Subsysteme aus ebenfalls privatisierten Unternehmen der Maschinenbaubranche vergleichend untersucht. Mittels dieses Vorgehens haben die Autoren versucht einen Beitrag zur Klärung der Frage zu leisten, auf welche branchenspezifische Besonderheiten es in dem spezifischen gesellschaftlichen und wirtschaftlichen Kontext Rumäniens ankommt, damit Öffnungsprozesse innovationsbezogen erfolgreich verlaufen. Dabei haben die Autoren feststellen können, dass Öffnungsprozesse im Rahmen der Maschinenbaubranche einem linearen hingegen in der Gasbranche einem nicht-linearen Verlauf folgen.
Keywords: 650; Openness; innovations; organizations; Romania; mechanical engineering industry; gas industry